A Bird’s Eye View on Rasaoushadhis in Panchakarma - H, Rahul; Kumar, K P Sajith; Bhat, Drishya H (International Research Journal of Ayurveda & Yoga, 2024)
Panchakarma, an inevitable part of Ayurveda, is a combination of 5 Shodhana procedures, namely Vamana, Virechana, Vasthi, Nasya, and Rakthamoksha. In addition to the above-mentioned Pradhana Karmas, Poorva Karmas such as Snehana and Swedana and Upakarmas such as Kavala, Pratisarana, and Dhoomapana are also a part of Panchakarma. These Shodhana procedures eliminate toxins in the body and make three doshas in equilibrium. Usually, Sthavara and Jangama Dravyas are utilized for Panchakarma procedures. In the current scenario, the utility and application of Panchakarma therapies are getting importance around the globe. There is a wide range of formulations explained in Ayurvedic classics for conducting Panchakarma therapies, but it is observable and evident that few formulations for Panchakarma contain Rasaoushadhis. These are not much explained in Brihathtrayees. However, the Ayurveda classics having focus to Rasa Shastra such as Rasaratnasamucchaya, Rasatarangini, Rasendrachoodamani, and Ayurveda Prakasha explain the inclusion of Rasoushadhis in Panchakarma formulations. Rasoushadhis are a group of medicines having metals and minerals, which are considered to be highly potent and fast acting. Sphatika, Anjana, Parada, Gandhaka, Thutta, Shilajathu, Loha, Kasisa, and Tankanaetcare are some of the examples having classical references in Panchakarma procedures. So here, an attempt is made to compile and evaluate some of the formulations with Rasoushadhis that are used in various Panchakarma procedures. Mode of action can also be explained in terms of their Rasapanchaka, Veerya, Dosha Karma, and other Karmas.